2021
DOI: 10.1063/5.0039646
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of lubricant impregnated in a cavity of lubricant-infused surface

Abstract: A lubricant-infused surface (LIS) has been widely studied due to its potential in various industrial fields. However, the outermost lubricant layer of LIS is highly vulnerable to external shear force, which gradually degrades the slippery property. In this study, the shear flow-induced depletion of lubricant impregnated in a single cavity was experimentally investigated. The lubricant-filled three-dimensional cavity was exposed to a laminar channel flow. Temporal variations in the interfacial menisci inside th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…In 2021, Kim et al explored the loss of lubricant in the SLIPS porous substrate under the impact of continuous water flow. 134 The loss rate of lubricant will increase at first and then decrease until the lubricant is completely lost. Through this experiment, they found that the spherical cavity has better performance in retaining the lubricant because this shape can reduce the shear stress caused by water flow.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Kim et al explored the loss of lubricant in the SLIPS porous substrate under the impact of continuous water flow. 134 The loss rate of lubricant will increase at first and then decrease until the lubricant is completely lost. Through this experiment, they found that the spherical cavity has better performance in retaining the lubricant because this shape can reduce the shear stress caused by water flow.…”
Section: Discussionmentioning
confidence: 99%
“…A low-surface-energy and low-viscosity lubricant is used to fill the surface micro/nano-pore structure to form a lubricant layer of SLIPS to make the surface molecularly smooth, which is unable to provide an effective adsorption point for contaminants or bacteria on the surface 44 (Fig. 5(b)) Tables 1 and 2.…”
Section: Application and Performance Characteristics Of Slipsmentioning
confidence: 99%
“…23 Partially filled spherical cavities with lubricant exhibited a significant resistance to depletion with time compared to a cylindrical groove. 24 Thus, there is a need to further examine different groove geometries.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the studies considered the meniscus to be flat, which appears to be unrealistic. Considering the interfacial tension effect and flow dynamics at the interface, for rectangular grooves, narrower and deeper grooves aid in superior resistance to lubricant depletion with a larger L s . Partially filled spherical cavities with lubricant exhibited a significant resistance to depletion with time compared to a cylindrical groove . Thus, there is a need to further examine different groove geometries.…”
Section: Introductionmentioning
confidence: 99%